PERBANDINGAN NILAI AGREGASI TROMBOSIT PADA PASIEN HIPERTENSI YANG DIBERI ASPIRIN DAN TIDAK DIBERI ASPIRIN DI RSUP. PROF. DR. R. D. KANDOU MANADO - Ick, Beatrix Lusiana; Mongan, Arthur E.; Memah, Maya (Universitas Sam Ratulangi, 2014)
Abstract: Thrombocyte hyperaggregation occurs in hypertensive patients. Thrombocyte accumulates and thrombi formation caused by hyperaggregation are important factors in pathogenesis of cardiovaskular and cerebrovascular disease. Around 50 million people consume aspirin everyday to treat or to prevent cardiovascular or cerebrovascular disease. The use of aspirin known can increase bleeding risk especially when trauma occurs or intraoperative, but inhypertensive patients50 or over 50 years old, the benefit of aspirin can be greater then the bleeding risk it carries. Method: This study used comparative study, which compared thrombocyte aggregation value in hypertensive patients with aspirin and without aspirin. The tools that used for thrombocyte aggregation examination is an aggregometer and the data analysis is done by using SPSS software. Result: The difference value of thrombocyte aggregation in hypertensive patients with aspirin and without aspirin used T 2 independent samples test gave significant for ADP 10 µM and 5 µM(p <0.05), respectively 0.001 and 0.01. Conclusion: There is a difference between thrombocyte aggregation value in hypertensive patients with aspirin and without aspirin. Mean value ofthrombocyte aggregation in hypertensive patients with aspirin is lower than hypertensive patients without aspirin. Keywords: thrombocyte aggregation value, hypertensive patients, aspirin. Abstrak: Pada pasien hipertensi terjadi hiperagregasi trombosit.Penumpukan trombosit dan pembentukan trombus akibat hiperagregasi merupakan faktor penting dalam patogenesis penyakit kardiovaskular maupun serebrovaskular.Sekitar 50 juta orang minum aspirin setiap hari untuk mengobati atau mencegah penyakit kardiovaskular dan serebrovaskular.Penggunaan aspirin diketahui meningkatkan risiko perdarahan terutama saat terjadi trauma ataupun dalam prosedur pembedahan.Akan tetapi pada pasien hipertensi yang berusia 50 tahun atau lebih manfaat aspirin diperkirakan lebih besar dari pada risiko perdarahan yang mungkin terjadi. Metode: Penelitian ini menggunakan uji komparatif, yaitu dengan membandingkan nilai agregasi trombosit pada pasien hipertensi yang diberi aspirin dan yang tidak diberi aspirin. Alat pemeriksaan agregasi trombosit menggunakan agregometer dan analisis data menggunakan program SPSS. Hasil: Perbedaan nilai agregasi trombosit pada pasien hipertensi yang diberi aspirin dan yang tidak diberi aspirin ditunjukan dengan nilai siginikasi untuk ADP 10 µM dan ADP 5 µM (p <0,05) yaitu masing-masing 0,001 dan 0,01. Simpulan: Ada perbedaan antara nilai agregasi trombosit pada pasien hipertensi yang diberi aspirin dan tidak diberi aspirin. Nilai rata-rata agregasi trombosit pada pasien hipertensi yang diberi aspirin lebih rendah dibandingkan nilai rata-rata agregasi trombosit pada pasien hipertensi yang tidak diberi aspirin. Kata Kunci: Nilai agregasi trombosit, pasien hipertensi, aspirin.